ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR SECARA SUKARELA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) tahun 2011-2013) - Utami, Syilvi Fajria; -, Zulbahridar; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine and analyze the factors that influence the voluntary auditor switching. Those factors are client’s size, audit fee, financial distress, audit opinion, auditor’s size, management change, company’s growth, and client’s complexity. The population in this study consists of manufacturing listed firms in Indonesia Stock Exchange in the period of 2011-2013. Sampling method used in this study is purposive sampling. A total sample during 3 (Three) years observation is about 136 samples firm. Hypotesis in this research are tested by logistic regression on SPSS 17. The results of this study show that audit fee, audit opinion, management change and company’s growth have influenced on voluntary auditor switching. While client’s size, financial distress, auditor’s size and client’s complexity have no significant influence to voluntary auditor switching.Keywords: auditor switching, client, management, auditor, company